2010
DOI: 10.1590/s0103-05822010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia com laser terapêutico após tonsilectomia

Abstract: Objective:The postoperative period of a tonsillectomy is usually very painful, requiring the use of painrelieving drugs. The aim of this study was to evaluate the efficacy of low-level laser therapy in post-tonsillectomy pain control.Methods: 18 children aged 5 to 15 years undergoing adenotonsillectomy between June 2005 and October 2006 were randomized to receive either local application of therapeutic laser immediately after surgery and 24 hours postoperatively (n=9) or routine analgesic drug therapy, if nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The results of 8 other studies that were studied in this review showed that LLLT was effective in reducing postoperative pain in patients with breast augmentation surgery, 26 inguinal hernia surgery, 27 tonsillectomy, 28,31 episiotomies, 29 tibial fracture surgery 24 and coronary artery bypass surgery. 32,33 In addition, the laser can reduce the use of pain relief medication, thus protecting the patient from the complications of these drugs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The results of 8 other studies that were studied in this review showed that LLLT was effective in reducing postoperative pain in patients with breast augmentation surgery, 26 inguinal hernia surgery, 27 tonsillectomy, 28,31 episiotomies, 29 tibial fracture surgery 24 and coronary artery bypass surgery. 32,33 In addition, the laser can reduce the use of pain relief medication, thus protecting the patient from the complications of these drugs.…”
Section: Discussionmentioning
confidence: 83%
“…The effect size was only calculated in 4 papers, 24,25,29,31 and in other articles due to the absence of SD or VAS, was not calculated. [26][27][28]30,32,33 As well, in Santos et al 29 VAS measurement was performed twice; more than 2 hours after surgery, and after 40-48 hours after surgery. Therefore, one of these measurements was used to determine the treatment effect size.…”
Section: Effect Size Of Studiesmentioning
confidence: 99%
“…A meta-analysis conducted in 2019 indicates that PBM can be effective in modulating pain and inflammation following surgery, with the most efficacious results for postoperative pain after tonsillectomy [23]. Additionally, considering two previous studies that indicated a beneficial effect on pain modulation in tonsillectomy in adult [10] and pediatric populations [9], this clinical trial was conceived and proposed to the ethical committee. The PBM protocol proposed in this study differs from both studies cited above, in using 3 different wavelengths instead of 1, either 980 nm for adults or 685 nm for children, and a higher fluency (12 J/cm 2 in our protocol compared with 4 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study evaluated PBM efficacy in managing pain sensation after pediatric tonsillectomy and it demonstrated that in 9 patients treated with laser; nociception was significantly lower requiring fewer analgesic drugs in respect to untreated children (laser wavelength 685 nm, spot size 2 mm 2 , and fluence 4 J/cm 2 ) [9]. A more recent study [10] demonstrated, in 60 adults undergoing tonsillectomy, a significant reduction in pain sensation and in administration of analgesic drugs (laser wavelength 980 nm, spot size 2 mm 2 , and fluence 4 J/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…O efeito analgésico do laser é proveniente da inibição da formação do potencial de ação no nervo periférico, afetando a condução do estímulo nervoso, diminuindo ou interrompendo a transmissão dos impulsos evocados dos nociceptores para a medula espinhal (NEIVA et al, 2010).…”
Section: Introductionunclassified